IL-6 Genomic Variants and Risk of Prostate Cancer - Taheri, Mohammad; Noroozi, Rezvan; Rakhshan, Azadeh; Ghanbari, Molud; Omrani, Mir Davood; Ghafouri-Fard, Soudeh (Urology Journal, 2019)
Purpose: To evaluate the role of Interleukin-6 (IL-6) single nucleotide polymorphisms in prostate cancer (PCa) and benign prostate hyperplasia (BPH). Materials and Methods: We genotyped two IL-6 intronic variants (rs1800795 and rs2069845) in PCa cases, BPH cases and healthy men referred to Labbafinejad and Shohadaye Tajrish Medical Centers using tetra ARMS-PCR method. Results: The study included 130 PCa cases, 200 BPH cases and 200 healthy men. The C allele of rs1800795 was associated with PCa risk in the assessed population (OR (95% CI) = 1.45 (1.06-1.98)). However, the frequency of rs2069845 variants was not significantly different between PCa, BPH and control groups. The A C haplotype (rs2069845 and rs1800795 respectively) was associated with PCa and BPH risk (OR (95% CI) = 1.67 (1.12- 2.48); OR (95% CI)= 1.78 (1.25 – 2.54)). Besides, the A G haplotype (rs2069845 and rs1800795 respectively) has a protective effect against both PCa and BPH in the assessed population (OR (95% CI) = 0.63 (0.46-0.87); OR (95% CI)= 0.6 (0.45-0.79)). Conclusion: Consequently, the results of the current study provide further evidence for contribution of IL-6 in prostate cancer.